Kształtowanie się persko-muzułmańskiej tożsamości i pamięci historycznej w świetle historii relacji persko-muzułmańskich w „Kronice proroków i królów” at-Tabariego - Konik, Dariusz (Instytut Historyczny Uniwersytetu Wrocławskiego, 2022)
The aim of this article is to analyse the earliest interactions between Muslims and Persians, the portrayal of each group and the chronicler’s narrative surrounding them, in order to study the beginning of the process that would result in the creation of a dual Islamic Iranian identity and its core values.
Keywords: Persja Sasanidów; kalifat; islamizacja; arabizacja; at-Tabari